DESIGN AND IMPLEMENTATION OF NAVIGATION, MAPPING, AND BARCODE READING SYSTEM ON MOBILE ROBOT - Hanif Hibatullah, Muhammad
The main issue in warehouse management is the precision and accuracy of stock data, which is crucial for ensuring operational smoothness, especially in FMCG industries for example KKP ITB. Discrepancies in inventory can lead to disruptions in the production process and potential financial losses. Stock discrepancies can lead to production delays and potential financial losses. Factors contributing to these discrepancies include high workload for the employee, hindering effective stock data recording. The objective of this thesis is to develop an inventory system comprising navigation, mapping, and automatic barcode reading using a mobile robot, which is expected to enhance efficiency and accuracy in inventory management at KKP ITB's warehouse. The system design process involves several stages, including requirements analysis, system design, hardware and software implementation, and system testing. The system designed uses TurtleBot3 equipped with a camera to read barcodes using the pyzbar library. Hardware implementation involves the installation and configuration of components on TurtleBot3, while software implementation includes programming the robot's navigation, automatic mapping, and barcode reading. Testing is conducted in various scenarios to ensure the system's accuracy and reliability in performing the implemented functions. The implementation results show that this system can navigate in warehouse arena, perform mapping, and read barcodes automatically and accurately. This capability allows the system to be integrated with the existing inventory management system. Further development is recommended to improve the reading speed and the robot's navigation capabilities in more complex warehouse environments.